Impacts of surfactant-based adjuvants on spray droplet size, drift distance, and deposition efficiency - Gong, Changwei; Liu, Yue; Ma, Yu; Wang, Qiulin; Xu, Zhengze; Wang, Xuegui; Zhan, Xiaoxu; Shen, Litao (International Journal of Agricultural and Biological Engineering, 2024)
The application of anti-drift nozzles, such as air-induction nozzles, is the most common recommendation for reducing spray drift; To reduce the risk of coarse droplets bouncing and rolling produced by anti-drift nozzles, various types of adjuvants were screened by comparing their atomization performance, surface tension and contact angle, in order to identify favourable adjuvants that are compatible with anti-drift nozzles. It was found from the study results that the addition of 50% neem crude oil emulsifiable concentrate (neem oil), isomeric alcohol ethoxylates and BYK-405 all significantly decreased distribution span (S) and the percentage of droplet size less than 150 μm (ΦVol<150μ) values, but significantly promoted the median volume (D50) value. And the surface tension measurement results showed that all tested adjuvants significantly reduced the surface tension, while neem oil, FC4430 and silwetl-77 were observed with a most significant effects; Furthermore, all tested adjuvants except BYK-051N could also significantly decrease the contact angle, and the difference between neem oil, FC4430 and silwetl-77 was significant. Wind tunnel test results clearly demonstrated that the application of IDKA (a combination of air-induction nozzle IDK120-01 and neem oil) substantially decreased the drift deposition amount; In addition, the field experiments revealed that IDKA possessed a significantly improved deposition amount per unit area on canopy or bottom, leading to a more effective deposition. These results suggest that the use of IDK120-01 nozzle and neem oil can effectively reduce spray drift, lessen surface tension and enhance spreading. Keywords: spray drift, unmanned aerial vehicles, air-induction nozzles, surface tension, contact angleDOI: 10.25165/j.ijabe.20241703.7410Citation: Gong C W, Liu Y, Ma Y, Wang Q L, Xu Z Z, Wang X G, et al. Impacts of surfactant-based adjuvants on spray droplet size, drift distance, and deposition efficiency. Int J Agric & Biol Eng, 2024; 17(3): 50-58.